SPE Annual Technical Conference and Exhibition 1990
DOI: 10.2118/20697-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Design, Development, and Field Testing of a Water-Cut Meter Based on a Microwave Technique

Abstract: This paper will describe a new and unique instrument to accurately determine the water-cut of an oil-water emulsion. The basic principle of the measurement is based on a novel technique, commonly called oscillator load-pull, which detects the microwave characteristic of the emulsion. This measurement technique will be described simply and concisely. The design and development of the measurement pipe section and the necessary microwave oscillator source and control electronics will be discussed. Laboratory cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…For heavy crude oils, the use of microwave sensors are considered a better choice since water and oil absorb microwave energy differently and such a property is not affected by the oil density. …”
Section: Influence Of Water On the Emulsionmentioning
confidence: 99%
“…For heavy crude oils, the use of microwave sensors are considered a better choice since water and oil absorb microwave energy differently and such a property is not affected by the oil density. …”
Section: Influence Of Water On the Emulsionmentioning
confidence: 99%
“…Consequently, the potential to carry out non-intrusive, online measurements of water-cut in oil-water flows, led to microwave sensors gradually attracting the attention of scientists and engineers and have been proposed in a number industrial applications for multiphase flow measurements [12]. Yang et al [13] described an oscillator load-pull system to accurately determine the water-cut of an oil-water emulsion and presented the installation of the instrument and the field test results, but the watercut range was limited between 0-3% . Avila et al [14] determined water fraction from 0 to 100% by the frequency shift of the first resonant peak in a non-intrusive way based on a radio frequency resonant cavity sensor, however did not provide any details under flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These early application efforts produced promising results but also highlighted a number of areas requiring further study in order to understand the advantages and limitations of microwave sensors when used to monitor multiphase flow systems. The limitations/industrial drivers identified are related to: utilising the sensors during continuous flow and different flow regimes [13][14][15], the ability to accurately determine low water cuts [16], expansion of the measurement technique to non-homogenous systems [17], the large experimental errors resulting from certain configurations [18], the need to perform volumetric measurements [19] and the consideration of the influence of parameters such as temperature and salinity that can affect the measurements [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the watercut meter industry, different methods have been in use such as near-infrared technique (NIR) [12], microwave method [13][14][15], gamma tomography [16], and impedance measurements [17]. The impedance measurement method uses the impedance variation of the oil-water mixture for different water contents to obtain the watercut.…”
Section: Introductionmentioning
confidence: 99%